Acute respiratory failure following traumatic tooth aspiration. (7th February 2013) - Madan, Karan; Aggarwal, Ashutosh Nath; Bhagat, Hemant; Singh, Navneet
Abstract : Foreign body aspiration can infrequently occur following trauma. Tooth aspiration after trauma is a rare clinical scenario. Here, we report a case in which tooth aspiration after trauma led to a presentation of acute respiratory failure with clinical findings mimicking tension pneumothorax. Successful removal of the aspirated tooth was accomplished by rigid bronchoscopy. Tooth aspiration must be considered in the list of differential diagnosis for any patient having signs or symptoms of respiratory distress following trauma especially maxillofacial trauma.